IMPLEMENTATION OF LEARNING MANAGEMENT SYSTEM AT SEMEN TONASA JUNIOR HIGH SCHOOL TO SUPPORT DIGITAL LEARNING: MPLEMENTASI LEARNING MANAGEMENT SYSTEM PADA SMP SEMEN TONASA UNTUK MENDUKUNG PEMBELAJARAN DIGITAL - Asrul, Asrul; Baihaqi; Windayani, Windayani; Aprita, Ika Rezvani; Sri Agustina (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2025)
The advancement of digital technology has transformed the education sector, encouraging institutions to adopt technology-based learning systems. One viable solution is the Learning Management System (LMS), which aims to enhance the efficiency and effectiveness of the learning process. This Community Partnership Program (PKM) focuses on implementing LMS at SMP Semen Tonasa as part of the school's digital transformation efforts in teaching and learning activities. The methods employed include training and mentoring for teachers and students on LMS utilization, followed by an evaluation to assess its impact on engagement and learning outcomes. The program consists of several stages, including needs analysis, LMS installation, user training, and monitoring and evaluation. The results indicate that LMS implementation improves teacher-student interaction, facilitates easier access to learning materials, and enhances flexibility in the learning process. Evaluation findings reveal that 99% of participants understood the benefits of LMS after training. Additionally, the system allows students to access materials anytime and anywhere, fostering greater engagement in learning. Despite challenges such as adapting to a new system and infrastructure limitations, continuous mentoring helps overcome these obstacles. The LMSimplementation at SMP Semen Tonasa is expected to serve as a model for other educational institutions looking to integrate technology into their learning processes.